Vertical variability of aerosol single-scattering albedo and equivalent black carbon concentration based on in-situ and remote sensing techniques during the iAREA campaigns in Ny-Ålesund - Stachlewska, Iwona; Markowicz, Krzysztof; Chiliński, Michał; Lisok, Justyna; Ritter, Christoph; Cappelletti, David; Mazzola, Mauro; Makuch, Przemysław (Atmospheric Environment, 2017)
164 Nie dotyczy